Ungani Oil Field, Canning Basin - Evaluation of a Dolomite Reservoir. Issue 1 (1st December 2018) - Long, David; Esteban, Lionel; Millar, Amy; Forbes, Anne; Weston, Stuart; Kennedy, Martin
Abstract : Core supported study of the heterogeneous Ungani dolomite reservoir architecture is driving development drilling and upgrades to field resource estimates. Vuggy connected and macro non-connected pore space was directly measured over a 70m continuous core using 3D structural analysis of CT-scans. Plug density measurements indicate non-connected or sub-140 micron resolution contribution of around 1% to 2.5% (pu) for the tight matrix, but all remaining porosity potentially contributes to oil production. The high resolution core porosity data is vertically repositioned and upscaled to calibrate neutron-density and sonic petrophysically derived porosities which are inadequate to resolve productive zones using conventional reservoir cut-offs. Conditioned resistivity image data correlated exceptionally with directly measured connected porosities. Reservoir properties were extrapolated to all wells across the Ungani field giving field net/gross estimates of up to 63% and porosities over 30% pu in some vuggy and brecciaed zones. The heterogeneity and prolific nature of the uppermost 17m of reservoir had not been previously recognised due to poor log data coverage and access at the casing points. Recent re-analysis of this section at Ungani-3 with Chemostrat ICP-OES-MS analysis of ditch cuttings was instrumental in proposing additional drilling to re-target this zone. Mineralogy analysis is used to calculate rock grain densities and help calibrate neutron-density derived porosity logs over the Ungani field. Up-scaled core porosity correlates well with density and sonic porosity logs. Resistivity logs adjusted for minerology can also be used to predict porosity and support the use of resistivity image logs to identify vuggy zones and estimate porosity at a higher resolution than conventional logging tools. A field static model was populated with three facies distributed over vertical zones according to the distribution encountered in the core porosity analysis and well logs, and iteratively matched to the dynamic pressure data and field production history which exhibits field scale multi-Darcy horizontal permeability and protection from vertical water cut. Further drilling and downhole artificial lift is planned to extend field production rates to 3000 bbls/day. Increased confidence in this regionally developed reservoir is supporting further exploration of undrilled prospects in this immature and under-explored trend